Objective and subjective data on the real-world usage of pediatric robotic surgery in Germany - Ammer, Elisabeth; Schmedding, Andrea; Kahl, Fritz; Tüshaus, Ludger (Klinische Pädiatrie, 2025)
Twenty years after the first robotic pediatric surgery, robotic surgery still plays a limited role in pediatric surgery. A better understanding of the current application of robotic pediatric surgery, could be valuable for the further development and implementation of minimally invasive and robotic pediatric surgery. The aim of this study was to analyze the nationwide distribution of robotic surgery in children and its acceptance among pediatric surgeons. The national database of administrative claims data from the Institute for the Remuneration System in Hospitals (InEK) and the quality reports in Germany were analyzed to determine the number of pediatric patients who underwent surgery using a robotic system and the number of pediatric surgical departments having access to this system. Additionally, an electronic questionnaire was developed for a nationwide cross-sectional survey within the DGKCH. From 2019 to 2024, the number of robot-assisted surgeries in children increased from 105 cases in 2019 to 376 cases in 2024. The majority of procedures are urological surgeries. The online survey was completed by 39 pediatric surgeons between December 2022 and March 2023. The survey identified and mapped differences in the use of robotic systems, the patient population treated, and the assessment of outcomes, complication rates, and patient satisfaction. This study is the first to document the varying views on pediatric robotic surgery in Germany.
Keywords: pediatric surgery; robotic surgery; Germany; minimal invasive surgery; questionnaire